Pemantauan Tumbuh Kembang Anak Dan Penyediaan Makanan Sehat Bagi Balita - Sri Rahayu Rubyanto; Marhaeni DS; Choiril Hana Mustofa (Universitas Muhammadiyah Klaten, 2024)
Posyandu units are generally organized at the Rukun Warga or Hamlet level, according to the conditions of each area. Posyandu activities are carried out once a month in collaboration with the local Community Health Center to monitor the growth and development of toddlers and provide nutritious food for toddlers. Community service at Posyandu Margo Kencono VII, Kersan Hamlet, Sidorejo Village, is focused on socializing the use of Posyandu to monitor children's growth and development, prevent malnutrition and obstacles to children's growth and development. This community service also provides information about healthy, nutritionally balanced food for toddlers. , providing healthy food by mothers easily and cheaply using various ingredients that are available and easily obtained in the local community. Implementation of community service is carried out in a humane manner, by sitting together and discussing with mothers while waiting for their turn to weigh toddlers, record weight, height, arm circumference and head circumference, with material delivered on the use of Posyandu to monitor children's growth and development and provide food which is nutritious and mothers of toddlers are very enthusiastic about the posyandu activities.